Priming of cancer-immunity cycle by alleviating hypoxia-induced ferroptosis resistance and immunosuppression - Chen, Yun (2024)
Stimulating a robust cancer-immunity cycle (CIC) holds promising potential for eliciting potent and enduring immune responses for cancer immunotherapy. However, designing a therapeutic nanomaterial capable of both enhancing tumor immunogenicity and mitigating immunosuppression is challenging and often associated with complicated design paradigms and immune-related adverse effects. Herein, a multienzyme-mimetic alloy nanosheet incorporating palladium (Pd) and iron (Fe) is developed, which can prime effective CIC by overcoming ferroptosis resistance for enhancing tumor immunogenicity and reprograming the tumor microenvironment for enhanced second near-infrared (NIR-II) photoimmunotherapy. The nanosheets accumulate in tumors when administered intravenously and counteract hypoxia through catalase-like oxygen production and subsequent reduction of hypoxia-inducible factor-1α, M2-like macrophages, regulatory T-cell, and programmed death-ligand 1 (PD-L1) expression. The surface plasmon resonance of the nanosheets enables NIR-II phototherapy and photoacoustic imaging, coupling with its ferroptosis and tumor microenvironment reprogram properties to synergize with anti-PD-L1 checkpoint blockade therapy to achieve satisfactory antitumor outcome. This study offers a strategy for localized tumor treatment and boosting the CIC through a straightforward and inexpensive nanomaterial design.